El mundo de Max - Fernández Panadero, Javier, 1972-; Rienda Sevilla, Olga (Madrid : Editorial Páginas de Espuma, 2016)
Here you will find explanations to many things that happen around you along with hands on experiments with energy, light, perception, power, etc.
Online resource; title from ePub title page (Digitalia, viewed February 6,, 2018)
Keywords: Science -- Miscellanea -- Juvenile literature; Electronic books